ANALISIS TEKNIK WAWANCARA PENELITI DAN SURVEYOR PRODUK SUATU PROYEK (STUDI KASUS: PROYEK FACEBOOK MARKETPLACE) - Noorcahyani, Aliya (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2025)
Surveyor Product is a profession that does survey activity at a project. This activity (survey) has widened to the field of economics and business. A project has parties concerned such as surveyor, respondent, supervisor, representative team of product etc. Interview technique needs two parties to communicate to get a purpose of interview. Researcher and surveyor collaborates in the interview process. The aim of this study is to analyze some aspects of guideline interview and cognitive aspect in linguistics and survey method. Researcher uses descriptive qualitative method with in-depth interviewing technique to get information of project. Format verbatim interview and data analysis miles and huberman are used as explanation of discussion. Fomat verbatim interview is packed in the form of table. Secondary data is required to describe in more detailed primary data from the result of interview. Secondary data involves data source from all experts from linguistics and survey method and data analized by researcher. This research is second research from the project. First study discussed project process and the role of surveyor and social media in analyzing respondent. Second study is more emphasized on interview process that done by researcher and surveyor. The result is to know interview guideline and cognitive aspect in linguistics and survey method that can expedite the process of interview activity.